IL-17 in psoriasis: Implications for therapy and cardiovascular co-morbidities - Golden, Jackelyn B. (2013)
Psoriasis is a prevalent, chronic inflammatory disease of the skin mediated by cross-talk occurring between epidermal keratinocytes, dermal vascular cells and immunocytes, including activated antigen presenting cells (APCs), monocytes/macrophages, and Th1 and Th17 cells. Increased proliferation of keratinocytes and endothelial cells in conjunction with immune cell infiltration leads to the distinct epidermal and vascular hyperplasia that is characteristic of lesional psoriatic skin. Interaction of activated T cells with monocytes/macrophages occurs via the Th17/IL-23 axis and is crucial for maintaining the chronic inflammation. Recent epidemiological evidence has demonstrated that psoriasis patients have an increased risk of developing and dying of cardiovascular disease. Similar pathology between psoriasis and cardiovascular disease, including involvement of key immunologic cell populations together with release of common inflammatory mediators such as IL-17A suggest a mechanistic link between the two diseases. This review will focus on concepts critical to psoriasis pathogenesis, systemic manifestations of psoriasis, the role of IL-17 in psoriasis and cardiovascular disease and the potential role for IL-17 in mediating cardiovascular co-morbidities in psoriasis patients.